Pengembangan Etika Sosial Melalui Desain Instruksional Pendidikan Agama Islam (PAI) Kontemporer - ., Mukhibat (Literasi: Jurnal Ilmu Pendidikan, 2012)
This writing is expressions of the writer’s irritated feeling of tenageers’s social etique. It is indicated by their uncontrolled behavior in which they often conduct fighting with other tenageers. This event  is the portrait of the defact on social life. To cope this condition, it is required for religion educators with students’parents and the society leaders to internalize values of social etiques. One of ways is by teaching integration of social etique with religion. Hence, educators on education must develop instructional designs.  Contemporer of Islamic teaching can be realized through; (1)identify on their doubt on a particular value based on their need, (2) determine requirements and the alternative of problem solving, (3)choose the appropriate strategy of problem solving, (4)apply the strategy, (5)observe the effectiveness through evaluation, (6) revise the action. Beside that Islamic education teachers need to design the pattern of classroom management using socio emotional climate and practice the principle of effective classroom management such as identify students.Keywords: Islamic ethic, instructional designs.